Comparative Genomics and Transcriptomics of the Extreme Halophyte Puccinellia tenuiflora Provides Insights Into Salinity Tolerance Differentiation Between Halophytes and Glycophytes - Guo, Rui; Zhao, Long; Zhang, Kaijian; Lu, Huiying; Bhanbhro, Nadeem; Yang, Chunwu (Frontiers in Plant Science, 2021)
Halophytes and glycophytes exhibit clear differences in their tolerance to high levels of salinity. The genetic mechanisms underlying this differentiation, however, remain unclear. To unveil these mechanisms, we surveyed the evolution of salinity-tolerant gene families through comparative genomic analyses between the model halophyte Puccinellia tenuiflora and glycophytic Gramineae plants, and compared their transcriptional and physiological responses to salinity stress. Under salinity stress, the K+ concentration in the root was slightly enhanced in P. tenuiflora, but it was greatly reduced in the glycophytic Gramineae plants, which provided a physiological explanation for differences in salinity tolerance between P. tenuiflora and these glycophytes. Interestingly, several K+ uptake gene families from P. tenuiflora experienced family expansion and positive selection during evolutionary history. This gene family expansion and the elevated expression of K+ uptake genes accelerated K+ accumulation and decreased Na+ toxicity in P. tenuiflora roots under salinity stress. Positively selected P. tenuiflora K+ uptake genes may have evolved new functions that contributed to development of P. tenuiflora salinity tolerance. In addition, the expansion of the gene families involved in pentose phosphate pathway, sucrose biosynthesis, and flavonoid biosynthesis assisted the adaptation of P. tenuiflora to survival under high salinity conditions.